Chemistry of magnetic covalent organic frameworks (MagCOFs): from synthesis to separation applications. Issue 3 (14th January 2022) - Yadav, Priya; Yadav, Manavi; Gaur, Rashmi; Gupta, Radhika; Arora, Gunjan; Srivastava, Anju; Goswami, Anandarup; Gawande, Manoj B.; Sharma, Rakesh K.
Abstract : This review aims to explore the design, development and applications of magnetically supported covalent organic frameworks (MCOFs) in extraction of metal ions, nitro explosives and chemical pollutants. Abstract : Magnetic covalent organic frameworks (MagCOFs) represent a new class of emerging material, primarily employed in separation applications. Due to their attractive properties such as easy and cost-effective synthesis, high porosity, large surface area, strong π–π interactions between COF shells and facile magnetic recovery, MagCOFs are being widely deployed in adsorption applications and exhibited high adsorption performance. This review emphasizes on the key advancements in the synthesis of MagCOFs and documents their potential in diverse separation applications including nitro explosive treatment, heavy metal ion adsorption and extraction of persistent organic pollutants, poly aromatic hydrocarbons and endocrine-disrupting chemicals, among others. In addition to offering up-to-date research outcomes in the field of separation science by utilizing MagCOFs, this article also highlights the challenges and possible solutions in this exciting developing area of research.